Productivity of crossbred cattle on smallholder farms in southern Malawi - Agyemang, K.; Nkhonjera, L.P. (Springer, 1990)
A study undertaken to determine the performance of crossbred cows on the smallholder farms in southern Malawi with respect to reproductive and productive performance traits. Includes data on age at first calving, calving interval, and milk yield.